Case Report: Fremitus Nystagmus in Superior Canal Dehiscence Syndrome - Morrison, Miranda; Korda, Athanasia; Wagner, Franca; Caversaccio, Marco Domenico; Mantokoudis, Georgios (Frontiers in Neurology, 2022)
Superior canal dehiscence syndrome (SCDS) is a structural bony defect of the roof of the superior semi-circular canal into the middle cranial fossa and is responsible for the creation of a third window, which alters the dynamics of the inner ear. During humming, vibratory waves entering the vestibulum and cochlea are re-routed through the dehiscence, leading to stimulation of the otolithic and ampullary vestibular organs. This is responsible for the torsional-vertical nystagmus known as “fremitus nystagmus”. In this case report, we video-document a rare case of fremitus nystagmus and its resolution after plugging of the superior semi-circular canal.